Enhanced Sensitivity Mach–Zehnder Interferometer-Based Tapered-in-Tapered Fiber-Optic Biosensor for the Immunoassay of C-Reactive Protein - Lei Xiao; Xinghong Chen; Xuejin Li; Jinghan Zhang; Yan Wang; Dongqing Li; Xueming Hong; Yonghong Shao; Yuzhi Chen (Biosensors, 2025)
A Mach–Zehnder interferometer-based tapered-in-tapered fiber-optic biosensor was introduced in this paper. By integrating a micro-tapered fiber into a single tapered fiber structure, the design enhances sensitivity, signal-to-noise ratio, and resolution capability, while reducing the length of the sensing fiber. Through simulation analysis, it was found that the tapered-in-tapered fiber significantly improved the refractive index detection sensitivity by exciting a stronger evanescent field effect. The experimental comparison between the tapered-in-tapered fiber and traditional tapered fiber showed a 1.7-fold increase in sensitivity, reaching 3266.78 nm/RIU within the refractive index range of 1.3326 to 1.3414. Furthermore, to expand its application prospects in the biomedical field, glutaraldehyde cross-linking technology was used to immobilize C-reactive protein (CRP) antibodies on the surface of the tapered-in-tapered fiber, successfully creating a biosensing platform for the specific recognition of CRP. The experimental results demonstrate that this novel biosensor can rapidly and accurately detect CRP molecules at different concentrations with a detection limit of 0.278 μg/mL, and that it exhibits good selectivity and repeatability. This tapered-in-tapered fiber-optic biosensor provides new insights into the development of high-performance fiber-optic immunosensors and shows broad application potential in immunology research and early disease diagnosis.